The effect on blink frequency of a selective blue-filtering photochromic lens in patients with benign essential blepharospasm - Monschein, Tobias; Zrzavy, Tobias; Weber, Corinna; Kuzmina, Zoya; Gutstein, Walter; Sycha, Thomas (Frontiers in Neurology, 2023)
The aim of this clinical study was to assess the impact of a non-invasive selective blue-filtering photochromic lens coating Crizal Prevencia on the treatment and response of benign essential blepharospasm (BEB).Twenty-four patients were recruited in the outpatient clinic of the Medical University of Vienna in a randomized, double-blind, cross-over study design.Blink frequencies were assessed in patients with BEB before and respectively 14 days after intervention with either a filtering ophthalmic lens or a placebo lens.Outcome parameters include sub-group analysis of blink frequency under six different conditions: 3 photopic, resting, reading, and a video game condition.From 24 recruited patients, 15 patients were available for final analysis. Comparing the optical blue filtering lens to placebo, showed a reduced blink frequency in specific subtests, but not compared to baseline.In conclusion, optical filtering glasses migt have a beneficial effect on BEB and provide a noninvasive therapeutic add-on option, besides Botulinum neurotoxin therapy, for patients with BEB and should necessarily be further investigated in a multicenter setting resulting in larger sample sizes to gain valid information about the effect of photochromic blue filter glasses in BEB.